Reflections in Personal Construct Theory. - Butler, Richard (John Wiley & Sons, 2009)
The book aims to discuss different aspects of reflexivity by inviting well known practitioners to reflect on how reflexivity has impacted on their work. Each chapter will cover an aspect of personal construct theory which the author has found helpful in their work, its relation to reflexivity, how they have incorporated this in practice and how it has enhanced their understanding of their own self construing. Around 20 authors will be invited to contribute. . Dr Richard Butler is a Consultant Clinical Psychologist with East Leeds Primary Care Trust in the UK. He is an Associate Fellow of the B.